Breaking the of dormancy of ‘Daiane’ apples by using thidiazuron (Revista de Ciências Agroveterinárias, 2017)
The aim of this study was to evaluate the effect of different concentrations of thidiazuron (TDZ) combined with mineral oil (MO) or calcium nitrate on phenology, bud breaking and fruit production in ‘Daiane’ apple trees. The experiment was carried in Caçador, SC, during the 2013/2014 and 2014/2015 seasons. The treatments evaluated were control (without application); TDZ 250 mg L-1 + MO 3,5%; TDZ 125 mg L-1 + MO 3,5%; TDZ 250 mg L-1 + calcium nitrate 5%; hydrogen cyanamide (HC) 0,7% + MO 3,5%. A randomized block design was used, with six repetitions. The application of bud break promoters reduced the flowering period in 2013/2014 season, leading to a higher bud break of axillary buds than control in the two seasons. TDZ + MO was more effective for bud break in axillary buds than the other treatments. TDZ + MO and HC + MO had similar effect on bud break in terminal buds, with higher values than TDZ + calcium nitrate applications. In 2013/2014 season, the control and TDZ 250 mg L-1 + MO and HC + MO treatments showed similar fruit production, being higher when compared to the other treatments. For 2014/2015, the fruit weight was higher in plants submitted to applications of TDZ 250 mg L-1 + MO and HC + MO. The TDZ combined with MO is efficient in bud break induction of ‘Daiane’ apples, being a viable alternative to HC application.
Keywords: Malus domestica; bud break promoters; calcium nitrate; mineral oil; hydrogen cyanamide.